PENGARUH MEDIA PEMBELAJARAN AUDIOVISUAL TIKTOK TERHADAP PENINGKATAN HASIL BELAJAR PASSING BAWAH DAN PASSING ATAS BOLAVOLI SISWA KELAS VIII SMP NEGERI 2 ROGOJAMPI - Chandra Kusuma, Gilang; Hidayat, Taufiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of TikTok-based audiovisual learning media on improving the learning outcomes of underhand and overhead passing in volleyball among eighth-grade students at SMP Negeri 2 Rogojampi. This quantitative research used a quasi-experimental design with a posttest-only control group design, involving 80 students (39 in the experimental group and 41 in the control group) selected through purposive sampling. Data were collected through cognitive tests (multiple choice) and psychomotor tests (practical performance), then analyzed using the Mann-Whitney U test and effect size calculation. The results showed a significant difference between the two groups (p = 0.000; p < 0.05), with the experimental group achieving an average posttest score of 92.82 for knowledge and 78.82 for skills, compared to 70.12 and 72.41 in the control group. Effect size calculations yielded r = 0.815 (large category) for the cognitive aspect and r = 0.403 (medium category) for the psychomotor aspect. Thus, TikTok-based audiovisual media is proven effective in enhancing students' understanding and skill in volleyball passing techniques.